2004
DOI: 10.1016/j.femsle.2004.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a novel metalloprotease isolated from Aeromonas caviae

Abstract: A novel protease produced by Aeromonas caviae was purified and characterized. The molecular weight of the protease (AP19) was estimated as 19 kDa on SDS-polyacrylamide gel electrophoresis. The protease activity was not inhibited completely by heating at 100 degrees C for 15 min. The proteolytic activities were inhibited by metalloprotease inhibitor. The N-terminal amino acid sequence of AP19 was VTASVSFSGRCTN. AP19 did not activate Aeromonas proaerolysin, and did not show fluid accumulation in the rabbit intes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
1
5
1
Order By: Relevance
“…Other metalloproteases had been described in Aeromonas spp. For instance, Aeromonas caviae Ae6 metalloprotease was optimally active at pH 7.5 (Nakasone et al 2004), and a gelatinolytic metalloprotease from A. salmonicida showed optimal activity at 40°C and pH 7.5 (Arnesen et al 1995), which are different from that described here for protease K12. The enzyme characteristics of A. hydrophila strain K12 resembles that of some Bacillus species (Werlang and Brandelli 2005;Corrêa et al 2010) and is also similar to the Gram-negative Chryseobacterium sp.…”
Section: Resultscontrasting
confidence: 92%
“…Other metalloproteases had been described in Aeromonas spp. For instance, Aeromonas caviae Ae6 metalloprotease was optimally active at pH 7.5 (Nakasone et al 2004), and a gelatinolytic metalloprotease from A. salmonicida showed optimal activity at 40°C and pH 7.5 (Arnesen et al 1995), which are different from that described here for protease K12. The enzyme characteristics of A. hydrophila strain K12 resembles that of some Bacillus species (Werlang and Brandelli 2005;Corrêa et al 2010) and is also similar to the Gram-negative Chryseobacterium sp.…”
Section: Resultscontrasting
confidence: 92%
“…The size of the mature protein is in agreement with results from gel filtration chromatography and SDS-PAGE analysis (9) describing a protease of approximately 20 kDa and composed of a single polypeptide. The molecular mass of the mature AsaP1 is also in accordance with what has been described for the AP19 metallopeptidase of Aeromonas caviae (21) and the peptidyl-Lys metalloendopeptidases of Grifola frondosa and Pleurotus ostreatus, respectively (23). The AsaP1 sequence was found to be 91% identical to the sequence of A. hydrophila extracellular protease (Table 3), and Chang et al (3) reported that the A. hydrophila extracellular protease is detected as a 29-kDa protein in casein SDS-PAGE.…”
Section: Discussionsupporting
confidence: 85%
“…This property of the enzyme proved the role of Fe 2+ ions as cofactor of this enzyme. Fe‐metalloproteases were also reported for Aeromonas caviae and Chryseobacterium gleum . The inhibitory effect of some metal ions may be due to attachment with SH groups of Cys‐X breaking SS bridges thus changing the conformation of enzyme or may be due to the replacement with metals originally present in the enzyme structure …”
Section: Resultsmentioning
confidence: 88%